The Relation between Regional Government Supply Chain Management and Decision Making: Case Study on Regional Election in Indonesia - Dyah Purwanti; Sekar Mayangsari (International Journal of Supply Chain Management, 2020)
This research aims to explore the possible benefits of regional government supply chain management information towards decision making in regional election (“Pilkada”) in Indonesia. This research is important due to the rarity of researches that discuss the empirical and theoretical proofs of people’s needs towards government Supply chain management information. By using data from 2017 and 2018 regional election in Indonesia, I observed 198 regional governments at province/regency/city level. These sampled regions were chosen by deciding if the regional heads went to run for a second term. This decision was intended to evaluate the success of public policies applied in the first terms, which should be reflected in the regions’ government Supply chain management information that could be used by customers to consider if the ruling government (the incumbents) should be upheld or replaced. By using cluster analysis, I grouped the sampled regions into several clusters based on sociodemographic similarities. Then, I used discriminant analysis towards these clusters and found that regional government Supply chain management information has strong discriminant values towards regional election results. This research proves that customers have good awareness towards Supply chain management information involved in decision making. The implication of this research shows the existence of customers’ needs and interests towards regional government supply chain management information in regional election, thus regional government should improve the quality of supply chain management information and information dissemination, while also make sure that supply chain management information reaches and is reachable the whole society through vast publication and education.